EFEKTIVITAS METODE CERDAS CERMAT CEPAT DAN TEPAT (C3T) DALAM MENINGKATKAN MOTIVASI BELAJAR FIKIH - partono partono (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
This research is motivated by the large number of students who consider fiqh learning to be a boring learning and that alone is a monotonous alias. This causes the saturation of student learning to result in low motivation to study fiqh. This research aims to find out the effectiveness of the smart method, fast and precise in increasing the motivation to study Jurisprudence. The formulation of the problem in this study is how the effectiveness of the quick and accurate smart method (C3T) in increasing the motivation to study fiqh in MI Hikmatun Najah. This research is a qualitative descriptive study and the population is all of the students of MI Hikmatun Najah, with a total of 84 students. While the samples in this study were taken as many as 24 students from grade 3 at MI Hikmatun Najah who used conventional learning methods to become the control class and one of them in class 4, amounting to 17 students using the smart and meticulous learning method quickly and precisely as an experimental class. The instruments used in measuring the motivation of fiqh learning by using a questionnaire system. Then the data were analyzed using qualitative analysis techniques. Based on the results of the study showed that the intelligent method of fast and precise very effective in increasing the motivation of students to study fiqh.